Is the modern pig suited for organic production environments? - Olsson, Lina (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2010)
With a starting point in the legislation for organic production set up by the Swedish certification organization KRAV, the reasons to why these regulations are important is explained and how pigs are affected by these rules. The study also shows how well the pigs cope in the organic environment considering the origin of the genetic material; from the conventional pig population. The conclusion is that pigs do function fairly well in the organic production environment and the traits affecting their functionality involve: mothering abilities, strong legs, good meat quality, good sow durability and longevity, capacity to eat much roughage and dark skin color. There are however still many ways of improving the organic population of pigs to make them more adjusted to the organic environment; for example different traits brought into the breeding goals and the choice of good parent animals.